The Influence of Problem-Based Learning Model on Heat and Its Transfer Topic Toward Junior High School Students’ Problem-Solving Skills - Aprilia, Agnes Verena; Parmin, Parmin; Wusqo, Indah Urwatin (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
This study intends to reveal the influence of PBL on heat and its transfer topic toward the students' problem-solving skills and scientific attitudes. The design of this study was quasi-experimental with the nonequivalent control group. The samples consisted of the students of VII A (experimental class) and VII B (control class) selected using a purposive sampling technique. Data were collected through observation and tests. The results showed that the value of the correlation coefficient obtained based on the posttest of students' problem-solving skills was r = 0.728. Moreover, the t-test analysis on the value of the correlation coefficient of problem solving skill scored t count = 6.58, which indicated the existence of a dependent influence or relationship. The significance of the effect was seen from the coefficient of determination score of 56.25%. Besides, there were 75% of the students gave a positive response to the learning process. Thus, it concludes that the PBL on heat and its transfer topic has affected the students' problem-solving skills.